Implementasi Prinsip Ekonomi Islam oleh Pedagang dalam Melakukan Penimbangan Sembako di Pasar Bagan Hulu Rokan Hilir - Usnan Usnan (LPPM STAI Diniyah Pekanbaru, 2019)
This study aims to determine the implementation of weighing of the basic needs of traders following the perspective of the Islam Economy in Bagan Hulu Market Rokan Hilir District. The data analysis method used in this research is qualitative analysis with the normative and sociological approach. Research data obtained from the primary data and secondary data with data collection techniques in the form of observation, documentation, interviews. The results of this study indicate that there are still many traders in the market Bagan Hulu grocery that has not understood and even applies it following Islamic teachings. This is also related to the lack of government or religious institutions' concerns that offend or elevate Islamic business ethics into a system that will have a positive impact on the business they are running.